Leading and managing the lean management process - Fliedner, Gene (Supply and operations management collection., 2012)
Lean must be viewed as a comprehensive, integral system consisting of four interdependent elements: leadership, culture, team, and practices and tools. Each of these necessary components affects the effectiveness of the other components. This book examines these four elements utilizing a systematic, hierarchical orientation and explains their relevance for guiding internal Lean initiatives. This book serves as a core lean reference book. It offers a strategic framework beginning with the indentification and establishment of goals, followed with strategy development, and lastly tactical choices. This model framework is cognizant of a firm's relative internal strengths and weaknesses as well as external opportunities and threats. Each of the four integral Lean system elements is explored in depth. The model framework offers a path to develop Lean leaders with practical, actionable guidelines. The model framework is suited for applications in all industries. Throughout the book, the historical evolution of the current body of Lean knowledge is also examined as well as Lean's complementary initiative, Total Quality Management. A perspective that views Lean as a customer-driven philosophy for organization-wide continuous or ongoing improvement and waste elimination is maintained throughout the book. The book concludes with an exploration of Sustainability, the current Lean frontier as well as a discussion of Lean's future, the exchange of accurate and timely information among supply chain trading partners. This offering is different from other Lean books in three fundamental ways. First, it offers and develops a comprehensive lean model based on a sound framework. Second, it examines a historical timeline of significant lean contributions. Third, it extends Lean by offering a glimpse into its future.